PROSEDUR PENILAIAN KOPERASI BERPRESTASI PADA KOPERASI SE-KABUPATEN BULELENG PERIODE TAHUN BUKU 2020 BEDASARKAN HASIL LAPORAN RAPAT ANGGOTA TAHUNAN (RAT) - Dwipa, Kadek Angga; Sulindawati, Ni Luh Gede Erni (Universitas Pendidikan Ganesha, 2022)
This study aims to find out how the procedure for the Assessment of Cooperative Achievements in Cooperatives throughout Buleleng Regency for the 2021 Financial Year Period is based on the results of the Annual Member Meeting Report (RAT). The subject of this study is the Office of Trade, Industry and Cooperatives, Small and Medium Enterprises, Buleleng Regency. The object of this study is the Cooperative Assessment based on the results of the Annual Member Meeting Report. The data collection method applied consists of three types, namely the Observation method, the Interview method, and the Documentation method. The data analysis used in this study is qualitative descriptive analysis with data sources namely primary data and secondary data. The results of the study found that the procedure for evaluating outstanding cooperatives for the 2021 financial year period carried out by the Office of Trade, Industry and Cooperatives, Small and Medium Enterprises of Buleleng Regency was carried out properly and objectively. Each cooperative that is still active has collected a report book from the results of the Cooperative Annual Membership Meeting to the cooperative field section to input the data to find out how much the cooperative has achieved with certain aspects and requirements, namely: must deposit a report book from the results of the annual RAT related to the field of cooperatives and cooperatives must have passed the RAT.